International economics - Pugel, Thomas A. (McGraw-Hill Irwin, 2007)
This classic text covers all the conventional areas of international economics in an easy-to-understand manner. The 13th edition continues to provide the best blend of events and analysis, so that readers can build their abilities to understand global economic developments and to evaluate proposals for changes in economic policies. The book is informed by current events and by the latest in applied international research. Like earlier editions, it also places international economics events within a historical framework. The overall treatment continues to be intuitive rather than mathematical and is strongly oriented towards policy